AI: FRIEND OR FOE? DIGITAL LITERACY TRANSFORMATION FOR ENGLISH LEARNING AUTONOMY IN INDONESIA - Menggo, Sebastianus (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
The growing popularity of AI, facilitated by digital technology, provides enormous possibilities for transforming English teaching techniques for teachers inside and outside the classroom. AI promotes the integration of traditional teaching methods with digital technology-based instruction, leading to greater enthusiasm among students in learning English. Online learning remains the essence of learning as a platform for sharing information and transmitting humanistic values; more importantly, it is defined as a place to transform knowledge completely. This study aimed to examine the proficiency and obstacles to acquiring ICT literacy skills and English learning autonomy for secondary school pupils in Indonesia. A survey was undertaken with 574 secondary school students in Ruteng City, Indonesia. The data was gathered through the use of questionnaires and interviews and subsequently examined using both quantitative and qualitative methods of analysis. The study findings indicate that respondents possess a moderate degree of ICT proficiency. Twenty statements were utilized to assess the ability of ICT literacy, whereas ten questions were employed to gauge English learning autonomy. The respondents’ knowledge of ICT satisfaction was hindered by six factors: lack of enthusiasm and ownership in digital media knowledge, absence of affordability for internet data assistance, lack of funds to utilize specific English-language apps, untrustworthy internet connection, and inadequate ICT infrastructure at schools. Several barriers hinder respondents from achieving ICT literacy. Schools should overcome these hurdles and transform challenges into opportunities to enhance students’ English learning and academic achievement.